Influence of boron and molybdenum on yield attributes of mustard: Boron and molybdenum effect on mustard (Bangladesh Journal of Agriculture, 2023)
Boron and Molybdenum play a remarkable role in crop production and they are especially important for oil seed crops. Mustard is a very important oil seed crop in Bangladesh. The optimum and adequate levels of boron and molybdenum are very important for attaining a higher quality yield of oil seed crops. This study was carried out to investigate the influence of boron, molybdenum, and their interactions on yield and yield attributes of mustard var. Binasarisha-5 at the experimental field of Bangladesh Institute of Nuclear Agriculture, Mymensingh. Three levels of boron (0,1 and 2 kg/ha) and two levels of molybdenum (0 and 20 ppm) were used as treatment variables. Molybdenum was sprayed at the maximum vegetative growth stage. The experiment was laid out in a randomized complete block design with four replications. Results showed that the mean effects of boron and molybdenum significantly influenced the growth and yield of mustard. Application of 2 kg B/ha gave a significant influence on most of the yield contributing characters which resulted in the highest seed yield/ha (1294 kg/ha). Interactions of boron and molybdenum significantly influenced the seeds/siliqua, seed yield/plant, shoot weight/plant, shell weight/plant, seed yield /ha, straw yield/ha, and biological yield /ha. Seed yield (1337 kg/ha) was the highest with the interaction of 2 kg/ha application of boron and foliar spary of 20 ppm molybdenum. So, it is concluded that B and Mo application may increase the seed yield of mustard.Bangladesh J. Agri. 2023, 48(1): 101-111